2012
DOI: 10.1111/cas.12015
|View full text |Cite
|
Sign up to set email alerts
|

Importance of direct macrophage ‐ Tumor cell interaction on progression of human glioma

Abstract: We previously showed tumor-associated macrophages/microglia (TAMs) polarized to the M2 phenotype were significantly involved in tumor cell proliferation and poor clinical prognosis in patients with high grade gliomas. However, the detailed molecular mechanisms involved in the interaction between TAMs and tumor cells have been unclear. Current results reveal that, in coculture with human macrophages, BrdU incorporation was significantly elevated in glioma cells, and signal transducer and activator of transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
98
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 122 publications
(110 citation statements)
references
References 42 publications
9
98
0
3
Order By: Relevance
“…M-CSFR inhibition abrogates glioma progression by inhibiting the pro-tumor activation of TAMs (25). Although there have been a number of research studies regarding M-CSF production from glioma cells (26)(27)(28), to the best of our knowledge, there is no published research assessing M-CSFR expression in glioma cells, other than a previous study that reported the activation of M-CSFR in both glioma cells and TAMs in human glioma samples (8). The observations indicated that M-CSFR expression in cultured glioma cell lines is markedly lower than that in macrophages, and may suggest that M-CSFR expression in glioma cells may not be of particular interest for further research.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…M-CSFR inhibition abrogates glioma progression by inhibiting the pro-tumor activation of TAMs (25). Although there have been a number of research studies regarding M-CSF production from glioma cells (26)(27)(28), to the best of our knowledge, there is no published research assessing M-CSFR expression in glioma cells, other than a previous study that reported the activation of M-CSFR in both glioma cells and TAMs in human glioma samples (8). The observations indicated that M-CSFR expression in cultured glioma cell lines is markedly lower than that in macrophages, and may suggest that M-CSFR expression in glioma cells may not be of particular interest for further research.…”
Section: Discussionmentioning
confidence: 97%
“…It has been previously demonstrated that co-culture with macrophages induces activation of T98G cells; however, the gene expression profile of T98G cells was not evaluated (8). Therefore, in the present study, the gene expression of CCL2, IL-6, O(6)-methylguanine-DNA methyltansferase (MGMT), transforming growth factor-β (TGF-β), vascular endothelial growth factor-A (VEGF-A) and M-CSFR in control T98G cells and in the T98G cells isolated from a co-culture with macrophages was investigated by RT-qPCR.…”
Section: Enhanced Expression Of Ccl2 Il-6 and M-csfr By T98g Cells Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, little data is available to compare the phenotypes and behavior of microglia at tumor onset and during the late stage of glioma progression [28]. Similarly, it is difficult to observe the dynamic process of tumor invasion with the Transwell or Boyden chamber assay, an in vitro model that has recently been widely adopted in the study of glioma invasion and migration [10,29,30]. Compared to the Transwell assay, the obvious advantages of the newly developed microfluidic technology are the manufacture of chips in various forms to meet different experimental requirements and the ability to observe cellular behavior dynamically, temporally, and spatially in a controlled microenvironment [31].…”
Section: Discussionmentioning
confidence: 99%